2020
DOI: 10.1088/1361-6463/abc11e
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of MXene/polyaniline composites as promising anode materials for sodium ion batteries

Abstract: MXenes are one of the most promising electrode materials in energy storage devices owing to their unique properties, but the practical applications have been severely plagued by the low accessible electroactive area due to their inevitable restacking during electrode preparation. Recent experimental studies have reported that the additivepolyaniline (PANI) enables us to greatly improve the electrochemical performance of MXene-based electrodes. Herein, we systematically investigate the electronic, electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…For example, first-principles calculations were applied to explore the influence of additional PANI on the electrochemical properties of the electrodes (based on MXenes with different transition metal elements) for sodium-ion batteries. [250] It was found that numerous redox active sites were created with enhanced mass transfer in the electrolyte due to the suppressed restacking of the MXene sheets after the insertion of PANI. [250] Experimentally, Wang et al prepared a PANI/Ti 3 C 2 composite with a 3D interconnected network of high specific surface area (72.2 m 2 g À 1 , estimated by BET method) by self-assembly.…”
Section: Mxene-polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, first-principles calculations were applied to explore the influence of additional PANI on the electrochemical properties of the electrodes (based on MXenes with different transition metal elements) for sodium-ion batteries. [250] It was found that numerous redox active sites were created with enhanced mass transfer in the electrolyte due to the suppressed restacking of the MXene sheets after the insertion of PANI. [250] Experimentally, Wang et al prepared a PANI/Ti 3 C 2 composite with a 3D interconnected network of high specific surface area (72.2 m 2 g À 1 , estimated by BET method) by self-assembly.…”
Section: Mxene-polymer Compositesmentioning
confidence: 99%
“…[250] It was found that numerous redox active sites were created with enhanced mass transfer in the electrolyte due to the suppressed restacking of the MXene sheets after the insertion of PANI. [250] Experimentally, Wang et al prepared a PANI/Ti 3 C 2 composite with a 3D interconnected network of high specific surface area (72.2 m 2 g À 1 , estimated by BET method) by self-assembly. [251] The composite showed excellent electrochemical performance in a wide temperature range (from À 30 to 50°C) when applied as the active material in an anode for sodium-ion batteries.…”
Section: Mxene-polymer Compositesmentioning
confidence: 99%
“…However, SIBs have lower energy density compared to LIBs because sodium is heavier than lithium and has a higher standard electrode potential (−2.71 V versus SHE for sodium as compared to −3.02 V versus SHE for lithium) [8,9]. One of the greatest challenges is the significantly larger ionic radius (Na + : 1.02 Å, Li + : 0.76 Å) that often induces structural changes during Na + insertion and extraction, which causes storage materials to disintegrate and capacity to gradually fade [10,11]. Developing long-term stable, environmentally friendly storage materials based on abundant elements that provide high specific capacities and operate at a reasonable potential is considered a major challenge [12].…”
Section: Introductionmentioning
confidence: 99%
“…Since single-layer graphene was first discovered in 2004, twodimensional (2D) materials have aroused significant attention in various fields because of their specific 2D structures and diverse optoelectronic properties [1]. Since then, a group of 2D materials have been widely synthesized and investigated, including topological insulators [2], black phosphorus (BP) [3,4], hexagonal boron nitride [5,6], transition metal (TM) dichalcogenides (TMDs) [7,8], graphitic carbon nitride (g-C 3 N 4 ) [9], and transition-metal carbides/nitrides (MXene) [10,11]. In particular, materials composed of elements in the VA group (e.g.…”
Section: Introductionmentioning
confidence: 99%